The effects of relational capital on likelihood of conflict occurrence under the moderation effect of the propensity to trust - ATAMAN BERK, GÖKSEL (My University, 2023)
This study aims to contribute to the conflict literature by arguing that the relational capital between co-worker affect the likelihood of conflict occurrence and investigating the moderation role of propensity to trust on this interaction. A random sample was drawn from 381 Turkish citizen white collar employees from SME companies in nine industries. The study was prepared to measure employees\" perceptions of the conflict and relationship capital they experience with their co-worker, with whom they interact the most. According to the findings: 1) an increase in relational capital decreases the likelihood of task and relationship conflict occurrence; 2) relational capital decreases the likelihood of task and relationship conflict occurrence more when the levels of propensity to trust are high.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; İşletme; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; Management; İŞLETME; Ekonomi ve İş; Sosyal Bilimler (SOC); YÖNETİM; BUSINESS; ECONOMICS & BUSINESS; Social Sciences (SOC); MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; relational capital; propensity to trust; conflict predictors; relationship conflict; task conflict; CONFIRMATORY FACTOR-ANALYSIS; PERSONALITY-TRAITS; GENERALIZED EXPECTANCIES; INTRAGROUP CONFLICT; TEAM PERFORMANCE; JOB-PERFORMANCE; WORK GROUP; ANTECEDENTS; INNOVATION